Schlieren texture and topography induced confinement in an organic exciton-polariton laser - Florian Le Roux; Andreas Mischok; Francisco Tenopala-Carmona; Malte C. Gather (Nature Communications)
Abstract Non-linearities in organic exciton-polariton microcavities represent an attractive platform for quantum devices. However, progress in this area hinges on the development of material platforms for high-performance polariton lasing, scalable and sustainable fabrication, and ultimately strategies for electrical pumping. Here, we show how introducing Schlieren texturing and a rough intra-cavity topography in a liquid crystalline conjugated polymer enables strong in-plane confinement of polaritons and drastic enhancement of the lasing properties. In high-Q distributed Bragg reflector microcavities, polariton lasing was observed at unprecedented thresholds of 136 fJ per pulse. Morphology tuning also permitted polariton lasing in more lossy metallic microcavities while maintaining a competitive lasing threshold. The facile fabrication of these cavities will drastically reduce the complexity of integrating polariton lasers with other structures and the high conductivity of metallic mirrors may provide a route to electrical pumping.